The Effect of Blended Learning Type of Flipped Classroom on Mathematical Problem Solving Ability in Solid Figures Topic - Ahmad Ahmad; Lukmanul Akhsani (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2023)
This study aimed to find out the ability to solve math problems in solid figures topic before flipped classroom type blended learning was applied to grade IX students of SMPN 2 Sokaraja in the 2019/2020 school year and to know the influence of flipped classroom type blended learning on the problem-solving skills of solid figures topic in Grade IX of SMPN 2 Sokaraja in the 2019/2020 school year. By looking at the objectives, statistical testing was conducted to test the effectiveness formulated in the research hypothesis. To test the significance of mean differences over two different groups due to the use of multiple treatments on an independent variable can be done with a parametric statistical test using the -t-test. Before conducting parametric statistical tests, the data we obtained must fulfill the requirements of conducting tests with parametric tests including, normal and homogeneous distribution. If the data meets the requirements of a hypothesis test with a parametric test, but if it does not meet the requirements then the hypothesis test is conducted with a non-parametric test. The previous analysis resulted that the problem-solving skills of students taught with a blended learning model flipped classroom type are better than conventional learning models. Descriptively, when viewed from the average score of overall math problem-solving skills for students taught with a blended learning model flipped classroom type was 44.22, while those taught with conventional models was 38.17. From the average of each level of math problem-solving ability, the one taught with a blended learning model flipped classroom type was 4.42 and the one taught with conventional learning model was 3.82. It was explained, that the model of learning blended learning type flipped classroom was very influential on the ability to understand problems, the ability to plan solutions, the ability to complete, and the ability to re-examine the results of work